Significance of right ventricular function for the outcome of treatment and remodeling of the heart after LVAD implantation - Terzic, Dusko (Medicinski podmladak, 2022)
The efficiency of the device for permanent circulatory support of the left ventricle has been proven through clinical practice with the trend of constant improvement of treatment results along with biotechnological progress and improvement of surgical implantation techniques. The published reports of most reference cardiac surgery centers present a one-year survival rate of over 85%, a two-year survival rate of 70% and a five-year survival rate of 45-50%. In addition to clear benefits for the patient, LVAD implantation also carries significant specific risks, so infections, post-implantation bleeding, strokes, and right ventricular post implantation weakness are the most common complications. Given that the progress of the LVAD program is ensured primarily by reducing the incidence of complications not related to the functioning of individual segments of the cardiovascular system, and as left ventricular function is completely replaced by LVAD device, the most reasent challeng is the decision to install LVAD device in the heart with right ventricular given that the post implantation weakness of right vantricular is associated with proven increased mortality and morbidity. Since the 1990s, studies on hearts with implanted LVAD as a bridge to heart transplantation have shown regression of cell hypertophy, normalization of cell size, muscle fiber architecture, and heart chamber geometry. The described changes are characterized by the notion of reverse remodeling, which is synonymous with function recovery. It is this process at the level of the right ventricle that is recognized as extremely important for the success of LVAD programs, especially in the group of patients who have a certain degree of right ventricular weakness preoperatively. The basic requirements of the cardiac surgery team are adequate preoperative assessment of right ventricular weakness, then application of measures to prevent damage and load on the right ventricle during and after LVAD implantation, as well as providing adequate therapeutic measures for right ventricular recovery in the postimplantation period.